Concept Development Toolbox: Development of a methodology for structured and pragmatic concept development at Husqvarna Construction Products - Alfredsson, Matilda; Andersson, Olivia (My University, 2021)
Focusing efforts early in projects and working with structured and purposive methods can prevent changes in the later stages of product development projects, which can be costly and have detrimental effects for time-to-market. To maintain a strong market presence and competitiveness in R&D operations Husqvarna Construction Products are striving to continuously improve the time-to-market for complex product development projects. As a part of this endeavor, Husqvarna Construction Products wants to study improvement potentials in early project phases, with the goal to find ways to work more structured and purposive with concept development execution. The purpose of this project is to develop a Toolbox aimed to support structured and pragmatic development execution in early product development project phases where the conceptual design is performed. This project will support the improvement of early project phases as a part of Husqvarna Construction Products’ endeavor of reducing time-to-market for their product development projects. To achieve the purpose the research methodology comprised literature studies to research concept development methodologies, qualitative interviews to understand the current situation and needs at Husqvarna Construction Products and an iterative creation process for the Toolbox undertaken by an action-research approach involving participants from Husqvarna Construction Products. The Concept Development Toolbox comprises a methodology derived from established concept development methodologies, further adapted to suit the needs of Husqvarna Construction Products. The methodology’s core is to explore broadly, consider sets of solutions, and gradually narrow the sets by eliminating solutions, leading to convergence towards a final concept. It is influenced by the set-based approach, which supports considerations of several alternative solutions and prevents the appearance of late changes in the product development process. The Toolbox consists of two parts, a Handbook, and a Template. The Handbook aims to describe the methodology, the purpose, and how to execute activities. The Template aims to support the practical execution and facilitate documentation, by providing templates for each presented method and tool suggested in the Handbook. Concluding, the Toolbox is developed to support and facilitate structured and pragmatic concept development execution for Husqvarna Construction Products and a prerequisite for obtaining the benefits entailed from the Toolbox is to implement it in the current concept development processes at Husqvarna Construction Products. The Toolbox provides a baseline for continuous adaptations and improvement based on new needs and insights and the result presented now should be considered as a starting point in the endeavor of improving concept development execution at Husqvarna Construction Products.
Keywords: Concept development, Design methodologies, Husqvarna Construction Products, Set-based concurrent engineering, Product development.